ETIKA KEPEMIMPINAN DALAM PENGAMBILAN KEPUTUSAN DI MADRASAH: STUDI LAPANGAN PADA KEPALA MTSN 1 PAMEKASAN - Vemby Lamara; Mohammad Muchlis Solichin; Ali Nurhadi (Idaarotul Ulum, 2026)
This study aims to examine the ethics of leadership among madrasah heads when making decisions at MTsN 1 Pamekasan. The main focus of this study is the ethical values applied, the decision-making processes employed, and their impact on madrasah management. The method used in this study is a qualitative approach involving field research. To collect data, interviews, observations, and documentation were carried out, whilst data analysis utilised an interactive model encompassing data reduction, information presentation, and drawing conclusions. The findings of this study indicate that the headteacher applies ethical principles such as honesty, fairness, responsibility, and solidarity when making decisions. The application of these ethical principles contributes to the creation of a positive working environment, enhances trust among the madrasah community, and supports the success of institutional management. Nevertheless, there are several challenges, including time constraints in the consultation process and the pressure arising from decisions that must be made promptly. This study concludes that ethics in leadership plays a significant role in improving the quality of the decision-making process in madrasahs. Therefore, madrasah heads need to continue to enhance their ethical and leadership competencies in order to overcome various challenges in educational management. Keywords: ethical leadership, decision making, madrasah principal, Islamic education